Factors That Influence the Use of Accounting Information Systems - Ernawatiningsih, Ni Putu Lisa; Arizona, I Putu Edy (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
Quality of the company's annual financial reports does not only depend on the company's personal factors but also on effectiveness of the use of systems. From economic point of view, people of Sukawati are more involved in trading.Therefore, the existence of a village lending institution is necessary to support the business capital. Village Bank is a village-owned financial institution that performs financial functions and manages the funds belonging to the village in the form of savings and loans. It sets out the goals for investigating the factors influence the effectiveness of using accounting systems. Research approach uses a sampling approach that involves multiple linear regression evaluations and the use of random samples of interest. These survey patterns are staff using accounting data gadgets in credit status organizations in the Skawati district village. The results indicate that individual skills, user involvement, internal control, and organizational culture have positif effect to use Accounting Information Systems.